-46-8x=5(-7x+7)

Simple and best practice solution for -46-8x=5(-7x+7) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -46-8x=5(-7x+7) equation:


Simplifying
-46 + -8x = 5(-7x + 7)

Reorder the terms:
-46 + -8x = 5(7 + -7x)
-46 + -8x = (7 * 5 + -7x * 5)
-46 + -8x = (35 + -35x)

Solving
-46 + -8x = 35 + -35x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '35x' to each side of the equation.
-46 + -8x + 35x = 35 + -35x + 35x

Combine like terms: -8x + 35x = 27x
-46 + 27x = 35 + -35x + 35x

Combine like terms: -35x + 35x = 0
-46 + 27x = 35 + 0
-46 + 27x = 35

Add '46' to each side of the equation.
-46 + 46 + 27x = 35 + 46

Combine like terms: -46 + 46 = 0
0 + 27x = 35 + 46
27x = 35 + 46

Combine like terms: 35 + 46 = 81
27x = 81

Divide each side by '27'.
x = 3

Simplifying
x = 3

See similar equations:

| 3=5-2 | | 75+10=15h | | 2(1.5)-3y=2 | | 4u-6=-2 | | p-0.30p=25.20 | | -20=4w | | 8x+6x-20=60-6x | | 7x+4q=8+3q | | 2(y)+8=8 | | y=x^3-6x^2-36x+15 | | 8=0.25(-m-1) | | 3(-3+2x)=9 | | 3m+n=35 | | 3(x+1)+2(2x-6)=33 | | 3x^3+2x^2+-41x+-66=0 | | 8a-48=-6(-6-6a) | | 6(2-3x)=4(5x+7) | | 2(5*555*5)-56= | | 5y+60-9=12+8y-72 | | 200*50+20= | | 9m+5=9m+6 | | m=n-7 | | -34m=12 | | 2x-9y=-3 | | 0=12x+4.9x^2 | | 90-6x=100-8x | | 2(6x-6)+3=2(2x+3)+5 | | 8x-4=10x+19 | | 9xz^2-30xz-96x= | | -2x-7(c+3)=-93 | | 1(a-4)=2(2a+4) | | 8x-4=10+19 |

Equations solver categories